Hukum Bayi Tabung Dalam Agama Islam - Latifah; Karinda, Merlin; Vaira, Rizky; Daiyah, Isrowiyatun; Tunggal, Tri (Yayasan Pendidikan Tanggui Baimbaian, 2023)
The research method used is library research based on the Al-Quran, hadiths and decisions from MUI fatwas and laws related to legal sources regarding IVF laws in Islam. The sources taken are from several views of the law of artificial insemination in humans (IVF). One of them is according to the opinion of Prof. Dr. Masjfuk Zuhdi, Central MUI Decision. the decision of Nahdlatul Ulama was based on the results of the Alim Ulama National Conference Forum in Kaliurang Yogyakarta in 1981, the Muhammadiyah Tarjih Institute in 1980, the Islamic Fiqh Institute in 1986, which resulted in a conclusion with strengthened legal basis from the Al-Quran and Hadith. In the fatwa of the Indonesian Ulema Council (MUI) it is stated that if IVF with sperm and egg cells of a husband and wife is legal according to mubah law, it is permissible. This can happen because it enters into endeavors based on religious principles. However, the scholars forbid the use of IVF technology from married couples who use another woman's womb as a means and this is unlawful. The scholars emphasized that in the future, this might cause difficult problems related to inheritance. In their fatwa, the MUI scholars also made a decision if IVF derived from sperm that had been frozen from a deceased husband is also unlawful because it would cause problems related to determining lineage or inheritance. Meanwhile, the process of IVF originating from sperm and egg cells that do not originate from a legal husband and wife, the MUI fatwa has expressly stated that this is unlawful with the same status as opposite sex relations outside of legal marriage or adultery.